Shock-Related Deformation of Feldspars from the Tenoumer Impact Crater, Mauritania - Steven J. Jaret (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2010)
Shock-related textures in feldspars have been found in impactites from the Tenoumer impact structure, Mauritania. We see a range in features, from disruption of twin planes, to inclined deformation lamellae, to true Planar Deformation Features (PDF’s) which occur at multiple orientations to one another. Most notably, these textures occur in samples that do not contain shocked quartz, suggesting feldspars record evidence of shock pressures lower than 8 GPa.
Keywords: Undergraduate Research; Pursuit